The SAP Material Master - a practical guide - Johnson, Matthew (Espresso Tutorials GmbH, 2017)
SAP Material Master – A Practical Guide • Understand SAP Material Master concepts and how to tailor it to • Receive tips and detailed expert guidance • Maximize your value stream through SAP Materials Management (MM) • Walk through practical implementation examples This book will explain basic concepts about how to tailor the SAP Material Master to your production environment, as well as detailed information on material master settings and their impact. This book provides the opportunity for readers to better understand their unique environment and how to make the SAP material master work for them. Veteran SAP Materials Management (MM) expert Matt Johnson provides best practices for how to approach common scenarios, in addition to cost saving tips. The book also touches on how material master settings can impact FI/CO.